Public perceptions of child pornography and child pornography consumers - Newman, Emily (2022)
Understanding the public’s perceptions of child pornography helps identify gaps in awareness and knowledge, impacts legislative decision making, quantifies stigmatization, and provides a baseline for identifying differences between lay and offender populations for clinical purposes. This research provides a comprehensive public survey assessing these issues. An Internet-based sample of 524 adults (mean age = 47 years, 51% female) within the USA were asked about their understanding and beliefs related to child pornography and individuals who view child pornography. The questions covered three topic areas—general perceptions of child pornography, endorsement of child pornography beliefs, and opinions related to the legality of various forms of child pornography as well as the decision making related to sentencing and sex offender registration for child pornography consumers. The research found that the public viewed these offenses as more severe than most other crimes and that there was an overestimation by the public of risks related to recidivism and contact offending. Additionally, the research found that there was support for most of the current sentencing guidelines in the USA, including sex offender registration, and that there was limited support for treatment over incarceration